2003
DOI: 10.1159/000068333
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Progesterone Receptors and Thyroid Hormone Receptors Alpha in the Ovine Diencephalon: No Effect of Estradiol

Abstract: Progesterone and thyroid hormones are key hormones in the control of reproduction in the ewe since both have been shown to inhibit GnRH secretion. GnRH neurons do not express progesterone receptors (PR) but half of them contain thyroid hormone receptors α (THRα), two nuclear receptors potentially able to act on gene transcription. PR and THRα distributions overlap in most regions of the ovine preoptic area (POA) and hypothalamus. To determine whether progesterone and thyroid hormones may also have common neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…A two-way ANOVA statistical analysis was performed using Prism, version 5 (GraphPad Software Inc.) to compare percentages of variation of Kiss tissular content related with controls for different incubation times and doses. neurones matched that previously described in the ewe hypothalamus (26,36) (Fig. 1).…”
Section: Discussionsupporting
confidence: 90%
“…A two-way ANOVA statistical analysis was performed using Prism, version 5 (GraphPad Software Inc.) to compare percentages of variation of Kiss tissular content related with controls for different incubation times and doses. neurones matched that previously described in the ewe hypothalamus (26,36) (Fig. 1).…”
Section: Discussionsupporting
confidence: 90%
“…Recent molecular studies suggest that the possible mechanism of estrogen-thyroid hormone interaction is mediated by cross-talk of estrogen and thyroid receptors and their respective ligands (Fujimoto et al, 2004). In addition, Dufourny and Skinner (2003) had demonstrated that Pr receptors and thyroid hormone receptors a (TH R-a) were coexpressed within the cells of ovine brain, and hypothesized that these hormones may act sinergisticaly to modulate different physiological functions, such as reproduction.…”
Section: The Effect Of Oeþpr On Thyroid Glandmentioning
confidence: 99%
“…Sex hormones are known to influence neuronal differentiation during fetal development. In adults, progesterone affects neuronal function by modulating gene transcription and cellular activity through classical intracellular receptors abundant in the CNS (Auger and De Vries, 2002;Blaustein, 2003;Coughlan et al, 2005;Dufourny and Skinner, 2003;Ghoumari et al, 2005;Gruber and Huber, 2003;Labombarda et al, 2003;Lonstein and Blaustein, 2004;Mani, 2006;Ozawa, 2005;Pierson et al, 2005). Progesterone, or its metabolite allopregnanolone, binds to a variety of intracellular receptors, including GABAA (Lambert et al, 2003;Pierson et al, 2005;Smith and Gong, 2005), the Sigma receptor (Baulieu, 1998;Maurice et al, 2001;Monnet and Maurice, 2006), 25-Dx (Meffre et al, 2005), and potentially others.…”
Section: Introductionmentioning
confidence: 99%